2016
DOI: 10.1521/pedi_2015_29_178
|View full text |Cite
|
Sign up to set email alerts
|

Impairments in Object Relations and Chronicity of Suicidal Behavior in Individuals With Borderline Personality Disorder

Abstract: While studies have demonstrated connections between impairments in object relations and self-destructive behaviors in individuals with borderline personality disorder (BPD), few have investigated whether these impairments relate to actual suicidal behaviors. The current study utilized the Social Cognition and Object Relations Scale-Global Method to investigate object relational functioning and suicidal behaviors in 131 residential treatment patients. Cognitive but not affective aspects of internalized represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…The SCORS-G is a coding procedure that may be applied to a range of narrative data, including performance-based testing narratives (Lewis et al, 2016; Whipple & Fowler, 2011), psychotherapy transcripts (Peters et al, 2006), or descriptions of relational episodes (Clemence & Lewis, 2018; Cogan & Porcerelli, 1996). It is designed to capture a range of cognitive and affective facets of social cognition using eight subscales that are rated on a scale from 1 ( pathological functioning ) to 7 ( healthier functioning ).…”
Section: Methodsmentioning
confidence: 99%
“…The SCORS-G is a coding procedure that may be applied to a range of narrative data, including performance-based testing narratives (Lewis et al, 2016; Whipple & Fowler, 2011), psychotherapy transcripts (Peters et al, 2006), or descriptions of relational episodes (Clemence & Lewis, 2018; Cogan & Porcerelli, 1996). It is designed to capture a range of cognitive and affective facets of social cognition using eight subscales that are rated on a scale from 1 ( pathological functioning ) to 7 ( healthier functioning ).…”
Section: Methodsmentioning
confidence: 99%
“…Scores for each of the eight subscales are calculated by averaging the ratings given on that dimension to each TAT card in the participant's protocol. A prior study utilizing data from the current sample identified two underlying component structures using principle component analysis (PCA), one representing affective-interpersonal aspects of object representations (with loadings from the AFF, EIR, EIM, AGG, SE, and ICS subscale scores) and a second related to cognitive aspects of object representations (with loadings from the COM and SC subscales) (Lewis, Meehan, Cain, Wong, Clemence, et al, 2016). Given that several recent studies have suggested the benefits of utilizing more global factor structures for the SCORS-G in comparison with the original eight subscale scores (Stein, Slavin-Mulford, Sinclair, Siefert, & Blais, 2012;Whipple & Fowler, 2011), in the present study we utilized the cognitive and affective component scores to investigate differences in suicide attempt history and personality style in our participant group.…”
Section: Methodsmentioning
confidence: 99%
“…Clemence and Lewis (2018) found that flexibility of internalized representations (e.g., the capacity to demonstrate a range of both positive and negative relational expectations) was associated with a significant reduction in suicidal ideation over the course of 5 years. However, other studies have failed to identify general differences in quality of internalized representations between suicide attempters and nonattempters (Lewis, Meehan, Cain, Wong, Clemence, et al, 2016), suggesting that other variables (such as personality style) may affect the influence of object relations as a risk factor for suicidal behavior. Blatt (2004;Blatt, Shahar, & Zuroff, 2001) emphasized the differential nature of object relations in anaclitic and introjective personality types.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…로르샤하 종합체계에서 정상 규준의 자료를 기준으로 수검 Table 1. Component of the Social Cognition and Object Relations Scale (SCORS-G) Bram, 2014Lewis et al, 2016Stein et al, 2012 Emotional aspects of representations Cognitive aspects of representations Affective-Interpersonal Cognitive Relational Self-affective Cognitive AFF COM AGG COM AGG SE COM EIR SC AFF SC EIR ICS SC EIM EIM EIM AGG SE AFF SE ICS EIR undergraduates (n = 63) residential patients (n = 131) outpatients (n = 59)…”
mentioning
confidence: 99%